UGT74D1 Catalyzes the Glucosylation of 2-Oxindole-3-Acetic Acid in the Auxin Metabolic Pathway in Arabidopsis - Tanaka, Keita (Oxford University Press, 2014)
IAA is a naturally occurring auxin that plays a crucial role in the regulation of plant growth and development. The endogenous concentration of IAA is spatiotemporally regulated by biosynthesis, transport and its inactivation in plants. Previous studies have shown that the metabolism of IAA to 2-oxindole-3-acetic acid (OxIAA) and OxIAA-glucoside (OxIAA-Glc) may play an important role in IAA homeostasis, but the genes involved in this metabolic pathway are still unknown. In this study, we show that UGT74D1 catalyzes the glucosylation of OxIAA in Arabidopsis. By screening yeasts transformed with Arabidopsis UDP-glycosyltransferase (UGT) genes, we found that OxIAA-Glc accumulates in the culture media of yeasts expressing UGT74D1 in the presence of OxIAA. Further, we showed that UGT74D1 expressed in Escherichia coli converts OxIAA to OxIAA-Glc. The endogenous concentration of OxIAA-Glc decreased by 85% while that of OxIAA increased 2.5-fold in ugt74d1-deficient mutants, indicating the major role of UGT74D1 in OxIAA metabolism. Moreover, the induction of UGT74D1 markedly increased the level of OxIAA-Glc and loss of root gravitropism. These results indicate that UGT74D1 catalyzes a committed step in the OxIAA-dependent IAA metabolic pathway in Arabidopsis.